Chief Executive Personality and Corporate Strategy and Structure in Small Firms - Miller, Danny; Toulouse, Jean-Marie (Management Science, 1986)
An empirical investigation of 97 firms was conducted to determine the relationships that three aspects of the chief executive's (CEO's) personality have with the strategies, structures, decision making methods and performance of their firms. CEO flexibility was associated with niche strategies, simple, informal structures, and intuitive, risk-embracing decision making. CEO need for achievement was related to broadly focussed, marketing-oriented strategies, formal and sophisticated structures, and proactive, analytical decision making. Executives with an internal locus of control pursued more product innovation, were more future oriented, and tailored their approaches to the circumstances facing their firms. The relationships between personality and organizational characteristics were found to be by far the strongest in small firms and also somewhat more significant in dynamic environments. Flexibility and locus of control related to corporate performance under certain conditions; need for achievement did not.